2017
DOI: 10.25217/numerical.v1i1.119
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Model Pembelajaran Attention, Relevance, Confidence and Satisfaction (ARCS) terhadap Kemampuan Berpikir Matematis berdasarkan Taksonomi Bloom Revisi

Abstract: Thinking mathematically is a way of thinking in accomplishing the AbstrakBerpikir matematis merupakan cara berpikir dalam menyelesaikan tugas matematika baik yang sederhana maupun yang kompleks. Hal yang terjadi pada penelitian ini, peserta didik kurang menyukai pelajaran matematika, kurangnya kesabaran pendidik dalam membimbing peserta didik, serta model pembelajaran yang kurang tepat dapat menyebabkan kemampuan berpikir matematis peserta didik rendah. Berpikir matematis Numerical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…So learning activities based on Revised Bloom's Taxonomy are effective for improving problem-solving skills. Furthermore, the results of this study are strengthened by research, showed that thematic learning in the perspective of Revised Bloom's Taxonomy could make the learning process more active and meaningful for students (Ardiani et al, 2013;Netriwati, 2018;Sari et al, 2017).…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…So learning activities based on Revised Bloom's Taxonomy are effective for improving problem-solving skills. Furthermore, the results of this study are strengthened by research, showed that thematic learning in the perspective of Revised Bloom's Taxonomy could make the learning process more active and meaningful for students (Ardiani et al, 2013;Netriwati, 2018;Sari et al, 2017).…”
Section: Resultsmentioning
confidence: 62%
“…Revised Bloom's Taxonomy emphasizes education to design curriculum, assessment, and suitability between the two, namely curriculum and assessment. Therefore it is important to apply physical learning in formulating learning objectives (Juhanda, 2016;Nursa'adah et al, 2016;Sari et al, 2017). Bloom's Revised Taxonomy has two dimensions, namely knowledge, and cognitive dimensions.…”
Section: Introductionmentioning
confidence: 99%